The U.S. factor in the evolution of the regional bipolar system on the Korean peninsula in the 1940s–1970s - D. A. Sadakov (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The U.S. policies toward the Korean peninsula during the Cold War are usually considered within the framework of the bipolar confrontation and the Soviet-American struggle for spheres of influence. Meanwhile, international interactions at the level of the Korean regional subsystem were not limited to a strict separation of states into two opposing camps and were characterized by greater complexity and unpredictability. This study attempts to show that U.S. policy was a determining, but by no means the only, factor in the formation and development of the regional subsystem of international relations on the Korean Peninsula and was flexible enough to adapt to the actions of other actors. The first section of the article examines how a relatively peaceful situation around Korea in the aftermath of World War II transformed into an intense superpower rivalry and division of the peninsula into two adversarial Korean states. The author notes that this export of bipolarity to Korea was actively promoted by the United States, seeking to prevent the excessive strengthening of the Soviet positions in the region. The second section examines the role of the United States in the Korean War and its subsequent settlement. It is emphasized that already then, contrary to its expectations, the United States faced opposition from a number of regional actors and realized the need to search for alternative strategies to participate in Korean affairs. The third section identifies specific steps undertaken by the United States to reduce its presence in South Korea and analyzes the response of regional actors to the changes in American foreign policy. In particular, it shows how the U.S.-Chinese rapprochement in the 1970s influenced the evolution of the regional security system toward multipolarity and détente. It is concluded that the U.S. regional policy in the 1940s and 1970s tended to be deliberately and gradually decreasing the degree of its involvement in Korean affairs due to the redistribution of commitments between allies and the engagement of new actors in the Korean settlement process. At the same time, the author notes that the strategic approach to Korean policy, chosen by the United States during the Cold War and based on a system of multilateral alliances, has remained relevant so far, helping the American leadership to effectively maintain its presence on the Korean peninsula.